Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1037/cou0000125
|View full text |Cite
|
Sign up to set email alerts
|

The ups and downs of being lesbian, gay, and bisexual: A daily experience perspective on minority stress and support processes.

Abstract: Daily diary methods were used to explore identity-related stress and support processes as they occurred from day-to-day in a sample of 61 lesbian, gay, and bisexual (LGB) young adults. At the end of each day for 7-10 consecutive days, participants reported on daily identity-salient experiences (ISEs), proximal minority stressors (internalized stigma, expectations of rejection), and affect (positive, negative). A multilevel latent covariate model was used to examine within- and between-person interrelations amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 45 publications
10
82
5
Order By: Relevance
“…While there is a robust body of evidence supporting the validity of the minority stress framework in relation to the mental health of lesbian/gay people (e.g., Fingerhut, Peplau, & Gable, 2010;Hatzenbuehler, Nolen-Hoeksema, & Erickson, 2008) as well as sexual minority people as a combined group (e.g., Lewis, Derlega, Griffin, & Krowinski, 2003;Mohr & Sarno, 2016), there is less evidence in support of the model to explain outcomes among bisexual people specifically, because across studies that have compared sexual orientation groups in this regard, bisexual people were found to report fewer discrimination events than gay or lesbian people (Bostwick, Boyd, Hughes, West, & McCabe, 2014;Herek, 2009;McLaren, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there is a robust body of evidence supporting the validity of the minority stress framework in relation to the mental health of lesbian/gay people (e.g., Fingerhut, Peplau, & Gable, 2010;Hatzenbuehler, Nolen-Hoeksema, & Erickson, 2008) as well as sexual minority people as a combined group (e.g., Lewis, Derlega, Griffin, & Krowinski, 2003;Mohr & Sarno, 2016), there is less evidence in support of the model to explain outcomes among bisexual people specifically, because across studies that have compared sexual orientation groups in this regard, bisexual people were found to report fewer discrimination events than gay or lesbian people (Bostwick, Boyd, Hughes, West, & McCabe, 2014;Herek, 2009;McLaren, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stress is considered a robust mechanism in health disparities (Adler & Rehkopf, 2008), and stigmatization, specifically, is a social stressor that is a "fundamental cause" of disease (Link & Phelan, 1995). Extensive research has demonstrated the negative effects of minority stress on sexual minority individuals and same-sex relationships, including increased risk for depressive and anxiety symptoms (Hatzenbuehler, McLaughlin, Keyes, & Hasin, 2010;Newcomb & Mustanski, 2010), maladaptive coping (Szymanski & Henrichs-Beck, 2014), emotional dysregulation (Mohr & Sarno, 2016), decreased social support and relationship quality (Cao et al, 2017), and increased feelings of hopelessness and worthlessness (Hatzenbuehler, Nolen-Hoeksema, & Dovidio, 2009).…”
Section: Minority Stressorsmentioning
confidence: 99%
“…Griffin (2012) indicates that many schools and other learning institutions are yet to come up with approaches to ameliorate the situation. For instance, Mohr and Sarno (2016), have shown that more than half (55% ) of LGBT individuals report felt insecure at school due to their sexual orientation and 38 percent felt insecure due to their gender identity.…”
Section: Problem Statementmentioning
confidence: 99%
“…Ideally, all relevant stakeholders ought to articulate plans to decrease bullying and inappropriate judgment towards LGBTs. This research therefore assesses efforts directed towards training school officials to respect the autonomy of LGBT community within the school setting; it also assesses existing laws directed towards the protection of this vulnerable group (Mohr and Sarno, 2016).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation